The Diallo verdict: another “tragic accident” in New York's war on street crime? - Harring, Sidney L. (Social justice, 2000)
Part of a special section on race, class, and state crime. The writer contends that the killing of Amadou Diallo was the outcome of aggressive and racist police practices that are deeply embedded in current New York police policy. He asserts that the acquittal by an Albany jury of the four police officers in the Diallo case was a travesty of justice, featuring at its center the Bronx district attorney's office inexplicable, even unbelievable, failure to challenge the police version of the facts. In addition, he contends that the trial acted as a context to legally justify New York's “aggressive policing” policy, concluding that the killing of Diallo was an “accident,” an unavoidable outcome of good police work. Finally, he provides details of the case as presented in court, the prosecution's failure to effectively challenge the NYPD's aggressive policing strategy, the expert testimony in the case, and the predictable reaction in New York to the acquittals.